Effects of Immunonutrition in Head and Neck Cancer Patients Undergoing Cancer Treatment – A Systematic Review - Tan, Sing Ean; Abdul Satar, Nur Fadhlina; Majid, Hazreen Abdul (Frontiers in Nutrition, 2022)
Background and Aims Malnutrition is prevalent among head and neck cancer (HNC) patients and leads to undesirable outcomes such as reduced treatment response and increased treatment-related side effects. This systematic review summarizes the recent evidence regarding the effect of immunonutrition in HNC patients undergoing radiotherapy and chemotherapy. Methods A literature search was conducted of the CENTRAL, ProQuest, MEDLINE, EBSCOhost, Web of Science and CINAHL databases; and further supplemented with internet and manual searches. Studies published between January 2011 and May 2021 were identified, screened, retrieved, and data extraction was performed. Results Twenty studies involving 1535 patients were included, 15 were randomized controlled trials (RCTs), three were retrospective study and two were comparative cohort studies. Five out of seven studies reported improvement or maintenance of nutrition status with continuous supplementation using immunonutrient-enriched formula. Three studies reported functional status as an outcome, with one study reporting significant improvement, one study reporting maintenance, and another study reporting no difference in the functional status of patients supplemented with immunonutrient-enriched formulas. Supplementation with glutamine did not reduce the overall incidence of mucositis but delayed the onset of oral mucositis and had significantly less incidence of severe oral mucositis. Conclusion Supplementation with immunonutrient-enriched formulas in HNC patients during radiotherapy and chemotherapy may improve or maintain nutrition status. Supplementation with glutamine during HNC radiotherapy and chemotherapy may delay the onset of oral mucositis and reduce incidences of severe oral mucositis. Further investigations are required, focusing on the timing, dosage, and duration of immunonutrition. Systematic Review Registration: PROSPERO, identifier CRD42021241817.